Effects of an endodontic auxiliary chemical substance on the bond strength of two methacrylate‐based endodontic sealers to dentin. Issue 6 (8th February 2017) - Fuzinatto, Roger Nicolini; Farina, Ana Paula; Souza, Matheus Albino; Miyagaki, Daniela Cristina; Randi Ferraz, Caio Cézar; Cecchin, Doglas
Abstract: Purpose: To evaluate the influence of irrigation protocols and drying procedures on the bond strength of two methacrylate‐based sealers to dentin and the associated failure pattern using scanning electron microscopy (SEM). Materials and Methods: Fifty single‐rooted human teeth were prepared with an irrigation protocol using either 5.25% sodium hypochlorite (NaOCl) or 2% chlorhexidine (CHX) and 17% EDTA (ethylenediaminetetraacetic acid) for smear layer removal. The following subgroups were also created based on drying of the root canal walls: paper points, the canals were blot dried with paper points with the last one appearing dry; or, ethanol, excess distilled water was removed with paper points followed by dehydration with 95% ethanol for 1 min and blotting with paper points. Each group was divided into two subgroups on the basis of the root canal sealer: EndoREZ and RealSeal SE. Bond strength was measured by the push‐out test. The data were analyzed by ANOVA/Tukey HSD ( α = 0.05). Failure patterns were classified as adhesive, cohesive, and mixed in the SEM analysis. The failure mode was evaluated by the chi‐squared test ( α = 0.05). Results: The roots irrigated with NaOCl showed significantly lower bond strength than the roots irrigated with CHX ( p < .05). RealSeal SE showed higher bond strength when compared with EndoREZ ( p < .05). The highest values of bond strength were in the CHX and ethanol groups with RealSeal SE ( p < .05). An increase in adhesive failure was observed in the NaOCl and EDTA group. Conclusions: The bond strength of both methacrylate‐based sealers is influenced by the irrigant protocol. Abstract : The roots irrigated with sodium hypochlorite showed significantly lower bond strength than the roots irrigated with chlorhexidine. The bond strength of EndoREZ and RealSeal SE is influenced by the irrigant protocol.